2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.004-418
|View full text |Cite
|
Sign up to set email alerts
|

Highest Dominant Frequency and Rotor Sites are Robust Markers for Atrial Driver Location in Non:invasive Mapping of Atrial Fibrillation

Abstract: Inverse-computed Dominant Frequency (DF) and rotor maps have been proposed as non-invasive mapping techniques to locate atrial drivers maintaining atrial fibrillation (AF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Many methods have been introduced in the literature to analyze EGMs. These methods are generally in three categories: signal processing techniques such as dominant frequency analysis and recurrence quantification analysis [ 8 , 9 , 10 , 11 , 12 , 13 , 21 , 22 ], machine learning and pattern recognition techniques such as principle component analysis, independent component analysis, linear discriminant analysis and quadratic discriminant analysis [ 15 , 16 , 19 , 20 ], and geometric approaches that infer the travel paths of electrical waves using LATs [ 17 , 23 , 24 , 25 , 26 , 27 ]. The proposed method belongs to the geometric category, as it tracks the most probable travel path using LATs, and identifies the focal source based on geodesic distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been introduced in the literature to analyze EGMs. These methods are generally in three categories: signal processing techniques such as dominant frequency analysis and recurrence quantification analysis [ 8 , 9 , 10 , 11 , 12 , 13 , 21 , 22 ], machine learning and pattern recognition techniques such as principle component analysis, independent component analysis, linear discriminant analysis and quadratic discriminant analysis [ 15 , 16 , 19 , 20 ], and geometric approaches that infer the travel paths of electrical waves using LATs [ 17 , 23 , 24 , 25 , 26 , 27 ]. The proposed method belongs to the geometric category, as it tracks the most probable travel path using LATs, and identifies the focal source based on geodesic distances.…”
Section: Discussionmentioning
confidence: 99%
“…Cantwell et al [ 7 ] surveyed the algorithms designed for identifying local activation times (LATs) and calculating the conduction velocity (CV) of electrical waves, and pointed out that estimating the uncertainty associated with the CV computation remains a challenge. In addition, the dominant frequency (DF) mapping method was used in a few studies to localize abnormal pacing sites of high frequency during AF [ 8 , 9 , 10 ]. However, Salinet et al showed that targeting the ablation site using DF could be unreliable [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Set G ,q|P = NaN and C ,q|P = NaN for 1 ≤ , q ≤ Q with = i 1 . 3 2. Sort the elements in C i1 according to their G-causality strength:…”
Section: First Iteration: Processing the Sons Of The Root Nodementioning
confidence: 99%
“…Several authors have investigated the inference of causality relationships among physiological signals. In particular, in electrocardiography the use of partial directed coherence to investigate propagation patterns in intra-cardiac signals was considered in [1], whereas Granger causality maps were built in [2,3]. In this paper, we propose a novel hierarchical causality approach to guide cardiologists towards candidate areas for cathether ablation and discriminate between normal (sinus rhythm) and abnormal propagation (rotors).…”
Section: Introductionmentioning
confidence: 99%